(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
The criminal decree in the ‘Cuatrecasas-Martínez’ case. A guide for the perplexed This article analyzes the canonical penal decree in the "Cuatrecasas-Martínez" case (known in the media as the "caso Gaztelueta "). The author posits that the procedure in question did not constitute a legitimate criminal trial, but rather an ad hoc disciplinary process. The study underscores several notable irregularities, including the extensive interpretation of Canon 1398 §2 and the imposition of a sanction that contravenes the principles of criminal legality and non-retroactivity. The article poses a question regarding the extent to which the authority of the papal institution can supersede fundamental legal principles and human rights. The research also identifies concerns regarding the management of evidence and an apparent reliance on the conclusions of secular courts. In conclusion, the decree appears to be a response to external pressures and media impact rather than a process that adheres to due process guarantees. SUMARIO: 1. Introducción - 2. Síntesis cronológica del caso - 3. El Decreto penal: descripción básica - 4. Presupuestos penales y procesales - 5. Las vinculaciones institucionales que determinan la pena: discriminación de los laicos - 6. La interpretación extensiva del tipo penal aplicable - 7. La pena asociada al tipo aplicable. Legalidad e irretroactividad de la ley penal - 8. Un lenguaje alegórico: no hay tipo penal aplicado, sino un singular procedimiento sancionatorio - 9. La práctica de la prueba - 10. A modo de conclusión.